The Relationship between Body Mass Index (BMI) and Gleason Score of Indonesian Prostate Cancer Men in Hasan Sadikin General Hospital - Abdurrahman, Fauzan; Suryanti, Sri; Sihombing, Aaron T (Journal of Medicine and Health, 2018)
The risk of high grade PCa in Asia in relation to BMI had positive or negative effect. The objective of this study is to know the relationship between BMI and Gleason score in Indonesian PCa patients. A cross sectional study was conducted in Hasan Sadikin General Hospital. The data were secondary data taken from medical records of prostate adenocarcinoma patients in Hasan Sadikin General Hospital. Ordinal data were analyzed using Chi square and correlation using Spearman. All calculation was done using SPSS 24. There were 95 Indonesian PCa patients. 78 patients is in normal BMI range. Of those 41 patients (52.6%) is in high level of Gleason score. 17 patients is in high BMI range. High Gleason score was found in 11 patients (P = 0.362; rs = 0.094). Conclusion, there is no relation between BMI in Indonesian PCa and Gleason score. Keywords : Prostate adenocarcinoma (PCa); BMI; Gleason score.